Impact of Political Instability on Social Development - Smith, Williamson (International Journal of Humanity and Social Sciences, 2024)
Purpose: The general objective of this study was to investigate the impact of political instability on social development. Methodology: The study adopted a desktop research methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive’s time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings reveal that there exists a contextual and methodological gap relating to the impact of political instability on social development. Preliminary empirical review revealed that political instability significantly undermined social development by disrupting essential services like education and healthcare, eroding social cohesion and trust within communities, and causing economic stagnation that increased poverty and unemployment. These disruptions created a vicious cycle that perpetuated poverty and inequality, hampering long-term sustainable development. The study emphasized the need for comprehensive strategies to address the root causes of political instability, such as strengthening political institutions, promoting good governance, and ensuring inclusive economic growth, with international support playing a crucial role in fostering resilient institutions and effective social development programs. Unique Contribution to Theory, Practice and Policy: The Modernization Theory, Dependency Theory and Social Conflict Theory may be used to anchor future studies on the impact of political instability on social development. The study emphasized the importance of integrating political variables into social development theories and recommended targeted interventions to address the root causes of instability. The study urged policymakers to prioritize political stabilization through reforms and resource allocation to social sectors. It highlighted the need for enhancing social cohesion, building economic resilience, and promoting inclusive governance to mitigate the effects of political instability on social development. Additionally, it stressed the role of international cooperation in supporting these initiatives.